Photographing of a Radiograph: A Simple Alternative - Matrishva B Vyas; Navin V Hantodkar (Wolters Kluwer Medknow Publications, 2011)
Photograph of a radiograph is customarily shot using "X-ray viewer" as a background. However, it has its own disadvantages in quality reproduction of image details. Method to use laptop screen as an alternative background for shooting photograph of a radiograph, is presented.